PENGARUH GAYA KEPEMIMPINAN TERHADAPMOTIVASI KERJA PEGAWAI EKSPEDISI POS TRUCUK JAWA TENGAH - Akka Latifah (Sekolah Tinggi Manajemen IMMI, 2018)
The Influence of Leadership Style on Work Motivation of central java expedition Post Office Employees. This study aims to determine the effect of leadership style on employee work motivation. The research sample at the central java expedition Post Office in the delivery section was 75 active employees. Analysis of the data used is simple linear regression analysis, hypothesis testing and analysis of the coefficient of determination, as well as the classical assumption test.This study is a quantitative study using questionnaire data that has been tested for validity and reliability, and the data analysis technique used to answer the hypothesis is simple linear regression analysis.Work Motivation (v) = 4.279 + 0.584 Leadership Style + e (error)The results of this study indicate that leadership style has an effect on employee work motivation at the central java expedition Post Office, as evidenced by the t value of 7.692 which is greater than t table of 1.992, with a significance value of 0.000, which is smaller than the level of significant 0.05; and a regression coefficient of 0.584. From the R Square value of 0.448 or 44.8%, it can be concluded that job satisfaction has an effect on the performance of central java expedition pos employees but is less significant.